Planning for Cikapundung Terrace Development in the Cikapundung River Watershed, Bandung City - Nyimas Riah Afrilianti; Rahmi Aprilianti Dewi (GoResearch - Research & Publishing House, 2023)
Bandung, as one of the centers of development in Indonesia, continues to transform to meet the increasingly complex needs of the community. One development project that has attracted attention is the